Pelaksanaan MS ISO 9002 Di Sekolah-Sekolah Di Kedah, Perlis Dan Pulau Pinang : Hubungkait Dengan Faktor Kepimpinan Sekolah - Maimunah, Husien (2001)

(untitled)
The main purpose of the study was to determine the relationship between school leaders' leadership for quality and the implementation of quality system MS IS0 9002 in education unit particularly at the school level. From the research the level of MS IS0 9002 activities implementation and the degree of school leaders' leadership for quality were determined. This research also enabled the comparison made toward leadership for quality based on term of service, gender and type of school served. Besides that it also explored the MS IS0 9002 implementation problems in schools. 21 schools in Kedah, Perlis and Pulau Pinang were studied in the research. Data for the level of MS IS0 9002 implementation and the degree of school leaders' leadership for quality were gathered using questionnaire self developed by the researcher based on "Pekeliling Kemajuan Pentadbiran Awam, PKPA Bilangan 1, 1997" and extensive literature review on the subject matter respectively. MS IS0 9002 implementation problems were obtained through structured interview. All quantitative data were analyzed using SPSS software. Result of the study proved that MS IS0 9002 implementation were influenced by the degree of leaders' leadership for quality where the higher the degree of leadership for quality the higher the level of MS IS0 9002 implementation. The level of MS IS0 9002 implementation was relatively low whereas the overall mean score of leadership for quality was high. The research also indicated that the degree of school leaders' leadership for quality differed based on term of service, gender and also type of schools served. Five major MS IS0 9002 implementation problems were time, documentation problems, not enough staff, negative perception on the quality system itself and also lack of highest management support.